Spectrum and resolvent of multi-channel systems with internal energies and common boundary conditions - Valiyev, A.A.; Valiyev, M.B.; Huseynov, E.H. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article the spectrum and resolvent of the so-called multichannel systems with nonzero internal energies were investigated. The spectrum and resolvent of multichannel Sturm-Liouville systems with nonzero internal energies m2i and general boundary conditions were investigated. These systems describe the propagation of partial waves in the theory of quantum physics. The importance of studying the spectral characteristics of these systems is presented in the well-known books of the theory of quantum physics. The finiteness of the number of eigenvalues was proved, the multiplicity of positive eigenvalues was investigated, and as well as the resolvent kernel of the system was found
Keywords: operator; eigenvalues; edge problem; Wronskian; transformation operator; asymptotics; continuous spectrum; resolvent; multi-channel systems; internal energy; quantum physics